STANDAR PELAYANAN MINIMAL PENDIDIKAN PERSPEKTIF REVOLUSI INDUSTRI 4.0 DI SD BAYAN ISLAMIC SCHOOL - Susanto Susanto; Muhammad Adlan Nawawi; Abdul Rohim (Institut PTIQ Jakarta, 2020)
This research is an exploratory study using a qualitative analysis approach. Data collection is done through; observation, interview, and documentation. The sampling technique was used by purposive sampling and snowball sampling. Data sources and research informants include; Principals, and Deputy Principals, Teachers, Parents Teachers Association, and Education Personnel. The results showed that (1) Application of Minimum Service Standards for Basic Education at Al-Bayan Elementary School was optimally fulfilled (2) SPM Dikdas' perspective of the industrial revolution era 4.0. First, in the realm of infrastructure is that there is a Smart Classroom that has internet access connectivity facilities in its learning. Second, the curriculum must be reoriented with some changes in competencies that must be possessed. Students must now have mastery of three benefits: data literacy, technological literacy, and human literacy. Third, educators apply to learn oriented to the Technological Pedagogical and Content Knowledge system (3) manifestation of the Implementation of Basic Education SPM perspective of the industrial revolution 4.0 era at SD Al Bayan the realization of computer and projector facilities to implement Smart Classroom despite the absence of internet access connectivity, the creation of technological literacy in learning Science, Mathematics, and English in the form of teaching materials in the way of interactive DVD Rom which is taught at school so students can learn anytime, anywhere. The creation of educators who implement a Computer Assisted Instruction system or learning utilizing Word Processor Learning.